Security standardisation research : 4th International Conference, SSR 2018, Darmstadt, Germany, November 26-27, 2018, Proceedings /: 4th International Conference, SSR 2018, Darmstadt, Germany, November 26-27, 2018, Proceedings. (2018) - Unknown
No abstract available